Decision Support System for Mall Nutrition Using Simple Additive Weighting (SAW) Method - Reni Nursyanti; . Mujiasih (International Conference on Engineering and Technology Development (ICETD), 2014)
The background of this research concerns the background by the number of severely malnourished children are increasing each year. Currently the data processing system and the calculation of the nutritional status of children under five are still using manual systems. Reporting nutritional status of children still using paper media which resulted in the frequent occurrence of data redundancy toddlers and infants often data loss occurs. To the authors conducted in-depth research that focuses on how to do the reporting and determination of the nutritional status of infants is more effective and efficient utuk always monitoring early childhood development. So in scientific research, the writer make an application determinants of nutrition in infants to help health centers in Mount harbor reporting and monitoring.This application method is used to support the assessment of nutritional status of children in health centers Mount Labuan is Simple Additive Weighting (SAW). SAW method is to find a weighted summation of rating the performance of each alternative on all attributes (Fishburn, 1967) (MacCrimmon, 1968). This method is the most famous and most widely used in dealing with situations of Multiple Attribute Decision Making (MADM). MADM itself is a method used to find the optimal alternative of a number of alternatives to certain criteria.